Evaluation of a foreign languages school hybrid program in Turkey through Stake's Responsive Evaluation Model - Gizem Bolcal Er; Kenan Dikilitaş (Literacy Trek, 2024)
In response to the onset of the COVID-19 pandemic, global educational institutions transitioned to fully online instructional modalities. Later, there was a gradual shift back to traditional educational formats. During this transitional phase, academic institutions adopted a hybrid delivery model, integrating elements of both online and face-to-face instruction. This study was conducted with students, instructors, and administrators affiliated with the Department of Foreign Languages at a state university, aiming to evaluate this department's hybrid program through Stake's Responsive Evaluation Model. In this program evaluation study, qualitative data were obtained through open-ended questions, narrative frames, metaphors, and drawings. A total of sixty nine students, eight instructors, and three administrators participated. Participants' positive and negative views were investigated, and suggestions were made to improve the current hybrid education program of the foreign languages school.